A study on the most chosen pathways by the students after they graduate both diploma and bachelor students. - Azlan, Azman; Esmadol, Mohd. Irfan; M. Zin, Mohd. Afiq (2010)
As university graduation in the future, one of the things that will be asked most often by everyone such as friends, family, and the occasional stranger on the street, is what as a graduate, intend to do after study. This question comes in many guises, such as "Where do you want to work?" to the "Do you have a job lined up already?" and even the "Don't you want to further your study?". It can be weird to go from the well-defined, structured life that we lead as a student for so many years into the uncertainty of life after graduate, but there is really no remedy for that fear and no way to stop those annoying questions aside from finding and settling into a job we will enjoy. The things that should to be concern are how we get to that point. The truth is, finding a career isn't always as easy as simply flipping open the classifieds and then applying for something. A truly successful job search is made up of many different steps, some of which start long before we're ever ready to send out our first resume. Hence, we need to plan. Planning is very important as we want to make our future look clear and be able to achieve all the objectives that have been plan. Therefore we are conducting this study to find out the best and most chosen pathways by students in UiTM Sabah. Hopefully this study will give some guideline to plan what we want to do after graduate whether we intend to further studies or directly working in particular sector.